Kajian Ma'anil Hadits Tentang Hukuman Mati Bagi Orang Murtad - Asrori Asrori (STAI ALHIKMAH Jakarta, 2018)
Discourse on the law of apostasy still leaves a debate. The text of the hadith explicitly states the execution of death for those who migrate from Islam, man baddal dīnahu faqtulūh. On the other hand the Qur’an gived a signal that there is no compulsion in Islam lā ikrāha fi al-Dīn. Humans have a prerogative to decide their choice without any intervention of other authorities. The dualism of the understanding of Islamic law resulting from these two contradictory above propositions requires further discussion in order to reveal the law given to apostates. This qualitative study attempts to expose the opinions of ulama on execution of death for apostates as well as attempts to compromise the dualism of understanding of religious texts above. Keywords: apostasy, dualism of Islamic law, Hadith Vol. XIV, No. 2, 2018 161 Abstrak Diskursus tentang hukum pindah agama (murtad) masih menyisakan perdebatan. Teks hadis secara tegas menyatakan eksekusi mati bagi mereka yang migrasi dari islam, man baddal dīnahu faqtulūh. Disisi lain al-Qur’an memberikan isyarat, bahwa tidak ada paksaan dalam islam lā ikrāha fi al-Dīn. Manusia memiliki hak prerogatif untuk menentukan pilihannya tanpa ada intervensi otoritas lain. Dualisme pemahaman hukum islam yang dihasilkan dari kedua dalil yang nampak kontradiktif diatas perlu adanya pembahasan lebih mendalam guna mengungkap hukum yang diberikan bagi orang murtad. Penelitian kualitatif ini mencoba untuk memaparkan pendapat ulama tentang hukuman mati bagi orang murtad serta usaha untuk mengkomprokikan dualisme pemahaman teks keagamaan di atas. Kata Kunci: Murtad, Dualisme Hukum Islam, Hadis